Assessment of Natural Radioactivity and Radiological Hazards in Brick Samples Used in Tiruvannamalali District, Tamilnadu, India, With a Statistical Approach. Issue 3 (September 2016) - Raghu, Y.; Ravisankar, R.; Chandrasekaran, A.; Vijayagopal, P.; Venkatraman, B.
Abstract : Abstract: The activity concentration of 226 Ra, 232 Th and 40 K in brick samples used in Tiruvannamalai District of Tamilnadu has been determined using gamma ray spectrometry. The activity concentration ranges from BDL to 16.02 Bq kg −1, 17.86 to 120.19 Bq kg −1, 240.09 to 481.35 Bq kg −1 for 226 Ra, 232 Th, and 40 K, respectively. The concentration of these radionuclides is compared with reported data from other countries. The radium equivalent activity (Raeq ), absorbed gamma dose rate (DR ), annual effective dose rate (HR ), annual gonadal dose equivalent (AGDE), criteria formula (CF), representative level index (RLI), activity utilization index (AUI), gamma index (Iγ ), alpha index (Iα ), the external hazard (Hex ), and internal hazard (Hin ) indices are calculated for the measured samples to assess the radiation hazards due to the use of these materials in the construction of dwellings. Multivariate statistical techniques (Pearson correlation, principal component analysis and cluster analysis) are used to study the relation between radionuclides and radiation hazards. The treatment of 14 radioactive variables sampled at 32 bricks by the factor and cluster analyses provided a possible interpretation of the collective data. The spatial distribution pattern of radionuclides has been depicted through the Kriging method using MapInfo software.